LOAF: Load and Resource Aware Federation of Multiple Sensor Sub-Networks - Sookyoung Lee; Mohamed Younis; Mohammed Alsolami; Meejeong Lee (IEEE Access, 2020)
Wireless sensor networks (WSNs) serving in hostile environments are susceptible to multiple collocated failures due to explosives, and natural calamities such as avalanches, landslides etc., which could partition the network into disjoint segments. A similar scenario is encountered when autonomous WSNs need to collaborate for achieving a common task; therefore, federating the segments or individual WSNs would be essential for sharing data between them. The federation may be achieved by populating relay nodes and providing perpetual inter-segment paths. In this paper, we tackle the federation problem while considering constrained relay availability that makes the problem more challenging. We exploit the use of a limited number of mobile relays to provide intermittent inter-segment connectivity. We propose LOAF, a novel algorithm for LOad and resource Aware Federation of multiple sensor sub-networks. LOAF strives to group the segments into multiple clusters considering the amount of energy consumed to support the inter-segment traffic as well as proximity between segments. The formed inter-cluster topology is star-shaped where the segments in each cluster are served by a distinct mobile relay and a central cluster provides inter-cluster data delivery. During forming a central cluster, LOAF opts to balance the load on the individual mobile relays in terms of energy consumed in travel and in wireless communication. We analyze the properties of LOAF mathematically and validate its performance through extensive simulation experiments.